Development of Modern World Economy Through The Prism of “Underdevelopment Whirlpools” - Elena Popkova (European Scientific Journal, ESJ, 2017)
The article analyzes the development of modern world economy through the prism of “underdevelopment whirlpools”. The author distinguishes the problem of disproportions of world economy development, provides the proprietary methodology of “underdevelopment whirlpools”, and studies the world economy through the prism of “underdevelopment whirlpools”. Based on the official statistical information of the International Monetary Fund, the author performs calculation of “underdevelopment whirlpools” in regional associations as a part of modern global economy: Advanced economies, of which the Euro area и Major advanced economies (G7) are distinguished and the Emerging market and developing economies, of which the Commonwealth of Independent States, Emerging and developing Asia, Emerging and developing Europe, Latin America and the Caribbean, Middle East, North Africa, Afghanistan, and Pakistan and SubSaharan Africa are distinguished. The article proves the thesis that modern global economy is peculiar for presence of deepening “underdevelopment whirlpools” that are largely determined by sectorial structure of economic systems.